Instructional Leadership : Principal's Challenges and Solutions in Enhancing Students' Academic Performance - Lani, Ahmad; Pauzi, Hezzrin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to investigate the principal's challenges and potential solutions for improving students' academic performance through instructional leadership. The qualitative approach is implemented by applying fragmentary observations, documents, and individual and group interviews The informants of this research were principals and teachers from two schools and one of the Indonesian community learning center. The data analysis technique used is thematic content analysis using ATLAS.ti software. The findings indicated that the principals' responsibilities in developing instructional leadership were categorized into five primary themes: concept, planning, program and execution, supervision, evaluation, and learning implication design. Challenges identified include schools' limited budget and the lack of teachers, students, and parents' problems. Some solutions discovered encompass optimizing the schools' budget, staff, and teachers, stakeholder collaboration and bipartite cooperation, student-teach-student, role modeling, counseling guidance, inspiring talks, and smart parenting. The principals recommended designing the school instructional leadership concept, formulating the planning, coordinating the program and its implementation, organizing the supervision and evaluation, constructing the learning implications, and identifying the challenges to secure solutions.